Gebyar Anak Peduli Sampah Sebagai Media Edukasi Pengelolaan Sampah Pada Anak-anak di Kelurahan Klitren Yogyakarta: - - Sekar Chairunnisa Purnomo; Alan Primayoga; Katherina Irene Dhamayanti; Joice Lumban Tobing; M. Vinda Nur Jihanto; Emy Setyaningsih (Forum Kerjasama Pendidikan Tinggi, 2023)
Environmental management problems, especially waste, are also experienced by Klitren Village, DI. Yogyakarta. To overcome these problems, Klitren Village has formed 16 waste banks in each RW. Still, the current waste bank management only collects and records waste volume from Klitren residents. The Waste Bank has not sought waste management education, especially in the early childhood age group. Therefore, the Purpose of Community Service (PCM) carried out by the PPK ORMAWA BEM IST AKPRIND Yogyakarta Team is to foster the habit of early childhood sorting waste and disposing of waste according to its type so that children are accustomed to maintaining personal and environmental hygiene. This PCM is packaged in the form of the Children Cares About Waste event at the Klitren Village as a medium for waste management education using four methods, namely: children's waste gymnastics, singing jingle children care about waste together accompanied by magic entertainment, storytelling, and questions and answers, waste sorting games and color fun. The activity was attended by 142 children, with details of 67 children aged 4-6 years and 75 children aged 7-10 years who came from representatives of 16 RW in Klitren Village. The method used in this activity is quite effective in educating early childhood. This can be seen from the children's enthusiasm in participating in all activities, especially for the waste sorting game. For children aged 4-6 years, on average, 80% of participants sorted leaf waste, and 70% of participants sorted plastic kup correctly. However, only 40% of the participants could sort the waste for the milk boks and straw waste correctly. Whereas children aged 7-10 years old, 90% had a good enough understanding to sort leaf waste; on average, 73% of participants managed to sort cardboard and plastic waste correctly.